Achilles and the tortoise : Mark Twain's fictions - Griffith, Clark, 1924- (University of Alabama Press, 1998)
& Nbsp;Covering the entire body of Mark Twain's fiction, Clark Griffith in Achilles and the Tortoise answers two questions: How did Mark Twain write? And why is he funny? Griffith defines and demonstrates Mark Twain's poetics and, in doing so, reveals Twain's ability to create and sustain human laughter. Through a close reading of the fictions-short and long, early and late-Griffith contends that Mark Twain's strength lay not in comedy or in satire or (as the 19th century understood the term) even in the practice of humor. Rather his genius lay in the joke, specifically the "sick joke